Multicenter, prospective clinical trial for balloon-occluded alternative infusion of cisplatin solution and fragmented gelatin particles of transarterial chemoembolization for hepatocellular carcinoma beyond up-to-seven criteria - Sodai Hoshiai; Naoyuki Hasegawa; Takeshi Yamada; Nobuyuki Takahashi; Kensaku Mori; Kouichi Mori; Kuniaki Fukuda; Daichi Takizawa; Bryan J. Mathis; Takahito Nakajima; Toshiyuki Irie (Scientific Reports)
Abstract Transarterial chemoembolization (TACE) is considered unsuitable for hepatocellular carcinoma (HCC) that exceeds up-to-7 criteria. Balloon-occluded alternative infusion of cisplatin solution and gelatin particles of transarterial chemoembolization (BOAI-TACE) has shown promise in the treatment of HCC and preservation of liver function. This prospective, single-arm study enrolled patients with HCC beyond up-to-7 criteria from five hospitals. The primary endpoint was objective response ratio (ORR) for BOAI-TACE, according to response evaluation criteria in cancer of the Liver (RECICL), at 2 months after treatment. Eighteen patients were enrolled in this study. Fourteen patients achieved response, resulting in an ORR of 77.8% (95% confidence interval [CI] 54.3–91.5%) according to both RECICL and modified response evaluation criteria in solid tumor (mRECIST) guidelines, meeting the primary endpoint. Disease control rate was 88.9% (95% CI 66.0–98.1%). No worsening of either Child–Pugh or albumin–bilirubin (ALBI) scores was observed. No serious adverse events were recorded, indicating that BOAI-TACE retains utility even in severe HCC cases while preserving liver function.